On the relationship between atmospheric water vapour transport and extra-tropical cyclones development. (August 2016) - Ferreira, Juan A.; Liberato, Margarida L.R.; Ramos, Alexandre M.
Abstract: In this study we seek to investigate the role of atmospheric water vapour on the intensification of extra-tropical cyclones over the North Atlantic Ocean and more specifically to investigate the linkage between atmospheric rivers' conditions leading to the explosive development of extra-tropical cyclones. Several WRF-ARW simulations for three recent extra-tropical storms that had major negative socio-economic impacts in the Iberian Peninsula and south-western Europe (Klaus, 2009; Gong, 2013 and Stephanie, 2014) are performed in which the water vapour content of the initial and boundary conditions are tuned. Analyses of the vertically integrated vapour transport show the dependence of the storms' development on atmospheric water vapour. In addition, results also show changes in the shape of the jet stream resulting in a reduction of the upper wind divergence, which in turn affects the intensification of the extra-tropical cyclones studied. This study suggests that atmospheric rivers tend to favour the conditions for explosive extra-tropical storms' development in the three case studies, as simulations performed without the existence of atmospheric rivers produce shallow mid-latitude cyclones, that is, cyclones that are not so intense as those on the reference simulations. Highlights: Model simulation of North–Atlantic extra-tropical cyclones. Several simulations with varying humidity initial and boundary conditions. Model is able to simulate the development and the approximate track of the storms. Dependence of the storms explosive development with atmospheric water vapour content.